KOMUNITAS IKAN DI PERAIRAN BUKIT SAPATHAWUNG KAWASAN PEGUNUNGAN MULLER, KALIMANTAN TENGAH - Haryono, Haryono - (Masyarakat Zoologi Indonesia, 2009)
Pegunungan Muller is an importantwater supply for three big rivers in Kalimantan (Kapuas, Barito & Mahakam rivers).These rivers support the local fish spurces; one of them is located in Bukit Sapathawung.The purposes of this study were to evaluate the fish diversity, abundance, distribution,its potency, and species status. The results showed there were 45 fish species belongingto 29 genus and 13 families; Cyprinidae was the dominant family. The species ofRasbora volzi was the most abundant reaching 14 ind./St., and Barbodes collingwoodiiwas the most locally distributed reaching 7.81%. Most of the species were commonfish species, in which 8 were endemic species of Borneo, 5 species as new records ofCentral Kalimantan, and 2 species are though to be new species. Almost all specieshad potency as consumed fish.